Carbon to diamond / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
On October 6, 2018, 200 UiTM students attended the ‘Car-bon to Diamond’ workshop which was organized by the Faculty of Applied Sciences (FSG), UiTM Perak Branch, Tapah Campus. The talk and sharing session with Amir Hamdzan Hamzah, the CEO of Detik Niaga became an eye opener and inspired the participants who were among the Semester 3 students of Diploma in Science programme of UiTM Perak Branch, Tapah campus. The participants were selected based on their previous semes-ter CGPA that ranges from 2.50 to 3.00.